2007
DOI: 10.3168/jds.2007-0171
|View full text |Cite
|
Sign up to set email alerts
|

Tanker Milk Variability According to Farm Feeding Practices: Vitamins A and E, Carotenoids, Color, and Terpenoids

Abstract: The aim of this work was to study the variability in the composition of bulk milk mixtures of fat-soluble compounds (vitamins A and E, carotenoids, and terpenoids) and assess the links with milk production conditions. Milk from 10 collection trips in the French department of the Haute-Loire (10 to 36 herds per trip) was sampled in the tanker twice during the winter period and 3 times during the grazing season. The collection trips differed in their altitude (440 to 1,150 m) and the forage system (grass or base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
80
3
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 18 publications
10
80
3
2
Order By: Relevance
“…The higher concentrations of α-tocopherol, β-carotene and unchanged concentrations of retinol in milk from the indoor feeding periods compared with the outdoor feeding periods were unexpected and in contrast to other studies (Lindmark-Månsson et al, 2003;Agabriel et al, 2007). Concentrations of fat-soluble vitamins in silage decrease during storage (Beeckman et al, 2010), and therefore lower values in milk would be expected during the indoor feeding periods.…”
Section: Effects On Fat-soluble Vitamins and Se In Milk And On Milk Scontrasting
confidence: 50%
“…The higher concentrations of α-tocopherol, β-carotene and unchanged concentrations of retinol in milk from the indoor feeding periods compared with the outdoor feeding periods were unexpected and in contrast to other studies (Lindmark-Månsson et al, 2003;Agabriel et al, 2007). Concentrations of fat-soluble vitamins in silage decrease during storage (Beeckman et al, 2010), and therefore lower values in milk would be expected during the indoor feeding periods.…”
Section: Effects On Fat-soluble Vitamins and Se In Milk And On Milk Scontrasting
confidence: 50%
“…A commonly known effect of season has been demonstrated by the data of Agabriel et al (2007) in French tank (bulk) milk. Milks produced during the grazing period were yellower than during winter feeding with preserved forages.…”
Section: Transfer Of Carotenoids To Bovine Fatsmentioning
confidence: 99%
“…Agabriel et al (2007) demonstrated the effect of season in French tank milks. Mean α-tocopherol contents were 18.8-21.7 and 10.5 mg kg -1 of milk fat between May and September, and in March, respectively.…”
Section: Transfer Of Tocopherols To Bovine Fatsmentioning
confidence: 99%
“…In particular, these fat-soluble vitamins present in organic milk are positively correlated with the animal feed, and the highest concentrations are found in grass, legumes, and other green plants [30,43]. Hence, as highlighted by many studies, organic milk is richer in alpha tocopherol and beta carotene (only present in cow's milk) than conventional milk.…”
Section: Nutritional Evaluation Of Organic Milk In the Diet: Some Conmentioning
confidence: 95%